Changes in the Plasma Membrane of Escherichia coli During Magnesium Starvation - Fiil, Annelise (1969)
The effect of Mg(++) starvation on the structure of the Escherichia coli cell membrane was studied with the freeze-etch technique. Special attention was paid to changes within the plane of the membrane, which in normal exponentially growing cells has a netlike arrangement of particles 2 to 6 nm in diameter. During Mg(++) starvation, a paracrystalline particle pattern appeared on the plasma membrane, and large areas devoid of particles were seen. Although these changes are reproducibly associated with Mg(++) starvation of the bacteria, no decrease in the Mg(++) content of the cell envelope per se was detected, even after 24 hr of Mg(++) deprivation. The structural changes caused by Mg(++) deprivation appeared to involve specific and permanent alterations in membrane development. The absence of other nutrients or divalent cations did not induce similar alterations.